Extracellular vesicles derived from host and gut microbiota as promising nanocarriers for targeted therapy in osteoporosis and osteoarthritis - Cheung, Kenneth Chat Pan; Jiao, Ma; Xingxuan, Chen; Wei, Jia (Frontiers in Pharmacology, 2023)
Osteoporosis (OP), a systemic bone disease that causes structural bone loss and bone mass loss, is often associated with fragility fractures. Extracellular vesicles (EVs) generated by mammalian and gut bacteria have recently been identified as important mediators in the intercellular signaling pathway that may play a crucial role in microbiota-host communication. EVs are tiny membrane-bound vesicles, which range in size from 20 to 400 nm. They carry a variety of biologically active substances across intra- and intercellular space. These EVs have developed as a promising research area for the treatment of OP because of their nanosized architecture, enhanced biocompatibility, reduced toxicity, drug loading capacity, ease of customization, and industrialization. This review describes the latest development of EVs derived from mammals and bacteria, including their internalization, isolation, biogenesis, classifications, topologies, and compositions. Additionally, breakthroughs in chemical sciences and the distinctive biological features of bacterial extracellular vesicles (BEVs) allow for the customization of modified BEVs for the therapy of OP. In conclusion, we give a thorough and in-depth summary of the main difficulties and potential future of EVs in the treatment of OP, as well as highlight innovative uses and choices for the treatment of osteoarthritis (OA).